Volkswagen's Localization Strategy: A Case of Rwanda’s Automotive Industry and Job Creation (British Journal of Multidisciplinary and Advanced Studies, 2025)
Volkswagen has effectively leveraged localization strategies across diverse global markets to enhance competitiveness and expand market reach. This paper examines Volkswagen’s strategic localization approach, with a particular focus on its impact on Rwanda’s automotive industry and job creation. By establishing an assembly plant in Kigali and integrating mobility solutions aligned with Rwanda’s economic and sustainability objectives, Volkswagen has played a pivotal role in shaping industrial development. This study employed a cross-sectional quantitative design to assess perceptions of Volkswagen’s localization strategy in Rwanda, focusing on its impact on the automotive industry and job creation. Surveys were distributed to 43 managerial-level employees at Volkswagen Mobility Solutions and 100 assembly plant employees to evaluate views on employment effects and localization effectiveness. Descriptive research design was used to systematically analyze responses, highlighting benefits such as job creation and changes in the industry landscape based on participants' perspectives. The findings from 80 respondents show that Volkswagen’s localization strategy in Rwanda serves as a model for companies and nations embracing sustainable mobility. Workforce development is a key factor in fostering self-sufficiency and economic progress while enhancing efficiency and competitiveness. While Volkswagen's efforts in employment, skill development, and alignment with national priorities are commendable, challenges related to community engagement and bridging the skills gap present opportunities for further growth. This study highlights the significance of localization in fostering economic growth, skill development, and sustainable transportation solutions.